UNDERSTANDING ORAL CORRECTIVE FEEDBACK IN EFL SPEAKING CLASSROOMS: EVIDENCE FROM INDONESIAN VOCATIONAL STUDENTS - Satrio Binusa Suryadi; Atiqah Nurul Asri; Farida Ulfa; Fitrotul Maulidiyah; Risa Juliadilla (Universitas Muhammadiyah Metro, 2026)
Oral corrective feedback linking speaking skills to communicative competence as an outcome of undergraduate students is still underexplored. Therefore, this study investigates oral corrective feedback on speaking skills among vocational college students. This study investigated vocational college students’ preferences for oral corrective feedback (OCF) in EFL classes. Using a mixed-methods design, the study involved students in non-English departments at a vocational college. An online questionnaire with Likert-scale scoring was used as Qualitative data to assess preferences for various OCF strategies. In contrast, semi-structured interviews for in-depth exploration are considered quantitative data. Questionnaire data were analysed using descriptive statistics (means and standard deviations), and interview results were thematically analysed. Findings indicated that students generally had positive perceptions of all types of OCF; however, elicitation, explicit correction, and requests for clarification emerged as the most preferred strategies. These forms of feedback were considered effective in improving comprehension of linguistic forms by promoting clarity and active engagement in the correction process. Interview results further revealed that students valued feedback that supported cognitive processing and confidence in speaking. In conclusion, this study highlights the importance of integrating direct and interactive feedback strategies in vocational EFL classrooms to support the development of language and communication skills in the workplace. These studies also offer pedagogical implications for language teachers and instructors to foster more adaptive and student-centred feedback practices.